SISTEM INFORMASI MANAJEMEN TAMAN KANAK-KANAK (STUDI KASUS : TAMAN KANAK-KANAK (TK) MEKAR SARI DESA AMBAWANG) - Meliana; Veri Julianto; Khairul Anwar Hafizd (Aisyah Journal Of Informatics and Electrical Engineering (A.J.I.E.E), 2020)
Current technological developments can be done to facilitate work. One of them can be applied to support management information system that focus on management TK Mekar Sari. The problems that exist in the process of acceptance of new students are still conventional (manual) and the class division process is still shared conventionally (manually) using Microsoft Excel. So it can take much time for class and student division in each semester. Based on the problem, the system is called